EVALUASI KESELAMATAN DAN KESEHATAN KERJA PADA PRAKTIKUM TEKNIK INDUSTRI UNIVERSITAS HASYIM ASY’ARI DENGAN METODE JOB SAFETY ANALYSIS - Mochamad Dwi Rizky Dharmawan; Sulung Rahmawan Wira Ghani (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2023)
Every year, the number of accident cases in Indonesia has been increased. The latest data in 2018 showed that there were 157,313 cases involving work accidents. In the fact, the laboratory is a place or room equipped with equipment for conducting experiments (investigations and so on). The manufacturing process of one of the practicums by using a machine can cause noise that is not appropriate with Occupational Safety and Health (K3) and the place is also inseparable from the potential dangers or even the risk of work accidents from the tools and practicum materials for the practitioner. There were efforts to prevent and minimize the work accidents in the laboratory, one of which is by applying the Job Safety Analysis (JSA) method and increasing the knowledge of K3 (Occupational Health and Safety). The purpose of this study is to know the application of JSA and the knowledge of K3 of work accidents in the Hasyim Asy'ari University laboratory. The method of this researcher was that identifying and analyzing the risks that occur. The results showed the sequence of work, potential hazards and control efforts made from each hazard. In short, the application of this method hopefully able to make the practitioner aware of the dangers that occur if they do not comply with the JSA (Job Safety Analysis) that has been made previously.